Starch from Pueraria lobata and the amylose fraction alleviates dextran sodium sulfate induced colitis in mice. (15th February 2023) - Yang, Yifei; Li, Mingxing; Liu, Qingsong; Zhao, Qianyun; Zeng, Jiuping; Wang, Qin; Zhao, Yueshui; Du, Fukuan; Chen, Yu; Shen, Jing; Luo, Haoming; Wang, Shengpeng; et al.
Abstract: Starch from Pueraria lobata (PLS) had polyhedral or spherical granules, displaying a bimodal size distribution within 0.6–30 μm. It showed a trimodal distribution of different molecular weight peaks, with amylose fraction of 18.2 %. PLS had a high crystallinity degree of 37.76 % and consisted of C-type starch, which gelatinized at 64.46–79.61 °C, with a high range of gelatinization (15.15 °C) and high enthalpy (13.98 J/g). A 21-day supplementation of PLS presented a regulative effect on gut microbiota in normal mice, and alleviated DSS-induced murine colitis through attenuating colonic inflammation, maintaining barrier function, preventing gut dysbiosis, increasing the short-chain fatty acids production and inhibiting NF-κB/IL-1β axis. The protective effect of PLS against colitis was in a gut microbiota-dependent manner. Notably, the amylose fraction was responsible for the prebiotic effect of PLS. The results would potentiate new application of PLS and the amylose fraction as functional prebiotics for prevention of colitis. Graphical abstract: Unlabelled Image Highlights: Pueraria lobata starch is structurally and physiochemically characterized. A 21-day supplementation of PLS presents a regulative effect on gut microbiota. PLS alleviates colitis in mice in a manner dependent on gut microbiota. The amylose fraction is responsible for the prebiotic effect of PLS. PLS and its amylose fraction is identified as functional prebiotics.